Dielectric response and anhydrous proton conductivity in a chiral framework containing a non-polar molecular rotor. Issue 48 (19th November 2015) - Yu, Shan-Shan; Liu, Shao-Xian; Duan, Hai-Bao
Abstract : A chiral 3D framework containing a nonpolar rotor shows two dielectric anomalies and can serve as a proton conductor under high-temperature and anhydrous conditions. Abstract : Herein, we report a chiral 3D framework with the formula [Co(HPO3 )2 ][H2 DABCO] (DABCO = 1, 4-diazabicyclo[2.2.2]octane). This compound exhibits two distinct dielectric anomalies, one attributed to the transfer of protons between non-polar DABCO and the inorganic framework, and the other to the in-plane oscillatory fluctuation of the DABCO molecule. It also exhibits proton conductivity under high-temperature anhydrous conditions.